PELATIHAN OBSTACLE AVOIDER ROBOT UNTUK PENGENALAN DUNIA ROBOTIKA BAGI SISWA SMAN 2 KABUPATEN TANGERANG - Guntara, Yudi; Fathia, Fathia; Harisudin, Ahmad; Anugrah, Azyumardi Rais (BEGAWE: Jurnal Pengabdian Masyarakat, 2023)
Integrating robotics into the education curriculum is a progressive step that can open doors for academic and student progress. The problems faced by extracurricular students at KIR SMAN 2 Tangerang Regency related to integrating robotics with academics have yet to be achieved. To facilitate students' academic and professional progress, the solution to this problem is to hold robotics training to introduce the world of robotics. The methods used include presentations, discussions, demonstrations, and practicums. The results of this research produced students who were able to assemble an Arduino obstacle avoider robot.